Exploring menstrual practices and potential acceptability of reusable menstrual underwear among a Middle Eastern population living in a refugee setting - VanLeeuwen C; Torondel B (International Journal of Women's Health, 2018)
Crystal VanLeeuwen, Belen Torondel Department of Disease Control, London School of Hygiene and Tropical Medicine, London, UK Purpose: Menstruation is a biological process that approximately half of the world’s population experiences over a significant period of their lifetime. As a displaced female, managing menstruation can be challenging as limited resources and changes in context confront the cultural norms of communities. This study explores the hypothetical acceptability and potential utility of a reusable menstrual underwear product through examining the beliefs, behaviors, and practices toward menstrual hygiene in a Middle Eastern population living in a refugee setting.Participants and methods: A qualitative study employing a questionnaire, semi-structured interviews, and focus group discussions was conducted with 30 refugee women and 5 humanitarian staff in Ritsona, Greece. All 30 refugee women completed a questionnaire, six refugee women and five humanitarian staff participated in individual semi-structured interviews, and four focus group discussions were held containing five to six refugee women per group. Inductive analysis led to the development of key themes.Results: Primary data analysis of narratives around the beliefs, behaviors, and practices of menstrual hygiene in this population revealed key themes related to the physical environment, the social environment, cleanliness, comfort, and health, and adaptation and coping. Themes related to the potential use of menstrual underwear included comfort, appearance, and concept, absorbent capacity and selected use, hygiene, and knowledge and implementation.Conclusion: Menstrual hygiene beliefs, behaviors, and practices are mostly consistent with existing literature. An acceptance of the concept of reusable menstrual underwear was expressed, although the perceived benefits of this product did not outweigh customary practices. The use of menstrual underwear as a complimentary product to traditional absorbents was expressed as helpful for promoting dignity. Keywords: menstrual hygiene, emergency, menstrual underwear, refugee, displacement, humanitarian emergency, humanitarian relief